Pretransplant Metabolic Distress Predicts Relapse of Acute Myeloid Leukemia After Allogeneic Stem Cell Transplantation. Issue 5 (May 2015) - Dietrich, Sascha; Radujkovic, Aleksandar; Stölzel, Friedrich; Falk, Christine S.; Benner, Axel; Schaich, Markus; Bornhäuser, Martin; Ehninger, Gerhard; Krämer, Alwin; Hegenbart, Ute; Ho, Anthony D.; Dreger, Peter; et al.
Abstract : Background: The impact of nutritional status on outcome of allogeneic stem cell transplantation (alloSCT) is controversial. This study investigates the influence of pretransplant weight loss and serologic indicators of nutritional homeostasis on relapse and death of acute myeloid leukemia (AML) after alloSCT. Methods: Pretransplant weight loss along with serum levels of total serum protein (TSP), albumin, C-reactive protein, and leptin were collected retrospectively in a training cohort (n = 149) and correlated with clinical outcome. Metabolic risk groups were defined and tested in an independent validation cohort (n = 167). Results: We identified pretransplant weight loss and TSP as strong independent predictors of relapse and death. Patients in the metabolic high-risk group (low TSP and weight loss) had an increased risk for relapse ( P = 0.0002) and death ( P = 0.002), but a similar risk for acute graft-versus-host disease. Weight loss coincided with reduced pretransplant serum leptin levels. The adverse influence of weight loss and high metabolic risk on relapse and overall survival could be confirmed in the validation cohort and similarly in patients with less than or more than 5% blasts before alloSCT. Multivariate analysis of both cohorts revealed a hazard ratio for relapse of 7.78 (2.59–23.36, P = 0.0003) in the metabolic high risk group. Conclusion: Altered nutritional homeostasis before alloSCT correlates with recurrence of AML after transplantation. Studies addressing pretransplant nutritional interventions to reduce AML relapse rates are warranted. Abstract : For stem cell transplant recipients with acute myeloid leukemia, this study of training and validation cohorts shows that pretransplant indicators of weight loss and low total serum protein predict worse relapse-free survival. Pretransplant nutritional intervention may influence outcomes. Supplemental digital content is available in the text.